Rise and Recharge: Effects on Activity Outcomes of an e-Health Smartphone Intervention to Reduce Office Workers’ Sitting Time - Abby Morris (International Journal of Environmental Research and Public Health, 2020)
This feasibility study evaluated the effects of an individual-level intervention to target office workers total and prolonged sedentary behaviour during working hours, using an e-health smartphone application. A three-arm (Prompt-30 or 60 min Intervention arm and a No-Prompt Comparison arm), quasi-randomised intervention was conducted over 12 weeks. Behavioural outcomes (worktime sitting, standing, stepping, prolonged sitting, and physical activity) were monitored using accelerometers and anthropometrics measured at baseline, 6 weeks and 12 weeks. Cardiometabolic measures were taken at baseline and 12 weeks. Fifty-six office workers (64% female) completed baseline assessments. The Prompt-60 arm was associated with a reduction in occupational sitting time at 6 (−46.8 min/8 h workday [95% confidence interval = −86.4, −6.6], p < 0.05) and 12 weeks (−69.6 min/8 h workday [−111.0, −28.2], p < 0.05) relative to the No-Prompt Comparison arm. Sitting was primarily replaced with standing in both arms (p > 0.05). Both Intervention arms reduced time in prolonged sitting bouts at 12 weeks (Prompt-30: −27.0 [−99.0, 45.0]; Prompt-60: −25.8 [−98.4, 47.4] min/8 h workday; both p > 0.05). There were no changes in steps or cardiometabolic risk. Findings highlight the potential of a smartphone e-health application, suggesting 60 min prompts may present an optimal frequency to reduce total occupational sedentary behaviour.